The Efficacy of Epley Maneuvers in the Management of Subjective Benign Paroxysmal Positional Vertigo in Sulaimany Governorate - Hemn Yaseen Mohammed; Yousif Ibrahim Al Chalabi (Advanced Medical Journal)
Background and objectives: Benign paroxysmal positional vertigo is vestibular disorder with most frequent episodes. It is mostly idiopathic.  Epley maneuver gives good results in most patients. The aim of this study is to confirm the diagnoses of benign paroxysmal positional vertigo by Dix-Hall pike test. And to evaluate the effectiveness of Epley maneuver in treating patients with this disorder.